EVIDENCE-BASED INPATIENT POSTNATAL CARE AMONG WOMEN IN A NATIONAL HOSPITAL IN KAZAKHSTAN: A BEST PRACTICE IMPLEMENTATION PROJECT - Colet, Paolo; Aimagambetova, Gulzhanat; Kossybayeva, Kapiza (JBI Evidence Implementation, 2020)
Improvements in reducing maternal and infant mortality in Kazakhstan have been noted over the past 2 decades. However, recent studies have indicated that care given to women during the perinatal period, which includes the postnatal period, is unsatisfactory. In addition, service delivery remains unstandardized, while outdated and inconsistent application of practice guidelines are observed in the clinical setting.
Keywords: Type of access: Open Access; clinical audit; evidence-based practice; implementation; Kazakhstan; quality improvement